Growth Patterns and Reproduction of Hampala Barb (Hampala macrolepidota) in Jatigede Reservoir, West Java Indonesia - Titin Herawati; Ayi Yustiatia; Atikah Nurhayatia (Indonesian Journal of Limnology, 2022)
The indigenous species of the Cimanuk River that can adapt to the stagnant waters of the Jatigede Reservoir is the hampala barb, this fish grows and breeds well; has an ecological function as a predatory fish from the cyprinidae family, and its economic function is that it can be traded in the Jatigede Reservoir, but its growth pattern, condition and reproduction factors are not widely known. The riset was conducted for six months (September - December 2017, January -  February 2018), the purpose of the research was to find the growth pattern, condition factors and reproductive characteristics of the hampala barb. Field survey research method, composite fish sampling from five research stations, data calculated using fisheries biology methods. The results showed that the growth was negative allometric. b value of male fish was 2.429; female fish was 2.717; good condition factor K value of male fish was 1.17 to 1.47 and female fish was 1.16 to 1.38. Reproduction is a partially spawn, starting to spawn in October.